2014
DOI: 10.1186/1752-0509-8-2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the lower protein limit in the budding yeast Saccharomyces cerevisiae using TIPI-gTOW

Abstract: BackgroundIdentifying permissible limits of intracellular parameters such as protein expression provides important information for examining robustness. In this study, we used the TEV protease-mediated induction of protein instability (TIPI) in combination with the genetic Tug-of-War (gTOW) to develop a method to measure the lower limit of protein level. We first tested the feasibility of this method using ADE2 as a marker and then analyzed some cell cycle regulators to reveal genetic interactions.ResultsUsing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Current studies have shown that disease genes tend to be highly connected among themselves in disease networks. These highly connected subgraphs could be disease protein complexes and investigation of the cause and effect of these complexes in disease networks could contribute to providing the search space for bioinformaticists, enhance the analysis process [5, 6] and help medical researchers to design new drugs. As a result, the detection of protein complexes plays an indispensable role in complex diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Current studies have shown that disease genes tend to be highly connected among themselves in disease networks. These highly connected subgraphs could be disease protein complexes and investigation of the cause and effect of these complexes in disease networks could contribute to providing the search space for bioinformaticists, enhance the analysis process [5, 6] and help medical researchers to design new drugs. As a result, the detection of protein complexes plays an indispensable role in complex diseases.…”
Section: Introductionmentioning
confidence: 99%
“…The galactose-inducible TEVp cleavage induced N-degron de-protection and consequently protein degradation by the proteasome. This flexible and fast system was applied to the study of cell cycle regulators (Sasabe et al, 2014), inhibition of 11β-hydroxysteroid dehydrogenase 1 (11β-HSD1) (Vanella et al, 2016) TEVp can be used as well to reactivate a protein function: for example, specific transcription factors can be introduced in a desired cell type to induce pluripotency (iPS technique), an approach proposed for cell replacement therapies. Delivery of such transcription factors can be achieved by fusing them to a protein transduction domains (PTD) as an alternative to viral transduction.…”
Section: Other In Vivo Tevp Applicationsmentioning
confidence: 99%
“…The recent advances in high-throughout technologies and systems biology approaches have provided huge amount of data showing the mutation heterogeneity in cancer cells [ 13 16 ]. A number of theoretical studies have been proposed to investigate the initiation and progression of cancer diseases [ 17 19 ]. Mathematical modelling has been used as a powerful tool to elucidate mechanisms in cancer initiation and progression [ 20 23 ].…”
Section: Introductionmentioning
confidence: 99%